High incidence of monozygotic twinning in infertility treatment - Sobek, Ales; Prochazka, Martin; Klaskova, Eva; Lubusky, Marek; Pilka, Radovan (Biomedical papers, 2016)
Background: Monozygotic twinning is associated with increased perinatal morbidity and mortality. There is evidence that the number of monozygotic twins increases after assisted reproductive techniques.Methods: We searched PUBMED, MEDLINE, and Scopus from 1987 to 2015 for studies analyzing the incidence and possible etiology of monozygotic twinning in infertility patients and critically reviewed the current state of knowledge.Results and Conclusions: Monozygotic twinning is a rare in natural conception but occurs around twice the normal rate after assisted reproduction. Factors associated with this phenomenon remain speculative, though there is some evidence that micromanipulation techniques, prolonged culture, and genetics are involved. In view of the possible complications, adequate pre-conception counselling is advocated.
Keywords: monozygotic twins; infertility; incidence; risk factors